Diagnosis of the nasolabial cyst: case report - Ana Rafaela Motta Moitinho; Cristiano Leal Rezende; Sarah Mascarenhas Souza; Arlei Cerqueira; Bruno Andrade Cantharino de Carvalho; Márcio Campos Oliveira
INTRODUCTION: The nasolabial cyst is classified in the group of non-odontogenic epithelial developmental cysts. Their occurrence is rare, however, they are located in the nasolabial sulcus, close to the alar insertion in the nose, external to the maxillary bone tissue. It is characterized as a floating tumor, generally asymptomatic, which promotes elevation on the nasal ala. OBJECTIVE: To report a case of nasolabial cyst addressing clinical, histopathological and radiological aspects, in order to alert professionals as regards their responsibility in diagnosis. MATERIAL AND METHOD: Female patient with a swelling in the region of the upper lip and nasal ala. After clinical examination, radiographic examination, puncture and aspiration, total surgical enucleation of the cyst was performed and the material collected was sent for histopathologic analysis. CONCLUSION: the dentist must be alert in order to make an early diagnosis, because it is not uncommon to overlook the lesion in the early stages.